2012
DOI: 10.1098/rspb.2011.2404
|View full text |Cite
|
Sign up to set email alerts
|

Linking genes to communities and ecosystems: Daphnia as an ecogenomic model

Abstract: How do genetic variation and evolutionary change in critical species affect the composition and functioning of populations, communities and ecosystems? Illuminating the links in the causal chain from genes up to ecosystems is a particularly exciting prospect now that the feedbacks between ecological and evolutionary changes are known to be bidirectional. Yet to fully explore phenomena that span multiple levels of the biological hierarchy requires model organisms and systems that feature a comprehensive triad o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
272
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 315 publications
(273 citation statements)
references
References 82 publications
1
272
0
Order By: Relevance
“…Daphnia are important organisms to address evolutionary responses to stressors as they are keystone species in aquatic food webs (Miner, De Meester, Pfrender, Lampert, & Hairston, 2012) and model species in ecotoxicology (OECD 2004). Moreover, as Daphnia produce resting eggs that are viable for many years, one can reconstruct evolution across decades (Orsini et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Daphnia are important organisms to address evolutionary responses to stressors as they are keystone species in aquatic food webs (Miner, De Meester, Pfrender, Lampert, & Hairston, 2012) and model species in ecotoxicology (OECD 2004). Moreover, as Daphnia produce resting eggs that are viable for many years, one can reconstruct evolution across decades (Orsini et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of a suitable model organism is particularly crucial. Cladocerans and monogonont rotifers both share a set of traits that make them ideal model organisms for the study of microevolution in metazoans (Fussmann, 2011;Miner et al, 2012). They are relatively small and easy to handle and culture.…”
Section: Introductionmentioning
confidence: 99%
“…The possibilities offered by this unique combination of traits have been intensively exploited in research on Daphnia (Miner et al, 2012). However, this is much less so in the case of monogonont rotifers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we address this issue using the water flea Daphnia magna and its symbiotic microbial community as a model system. D. magna is a keystone species in many freshwater habitats and has been widely used as an experimental system to study ecological and evolutionary interactions (for example, Decaestecker et al, 2007;Miner et al, 2012). Daphnia is known to harbor high numbers of bacteria on the surface of its body and in its gut (Grossart et al, 2010;Eckert & Pernthaler, 2014), and Qi et al (2009) showed that several bacterial taxa are consistently found in affiliation with Daphnia, even in geographically separated populations, indicating a highly specific association between Daphnia and its microbiota.…”
Section: Introductionmentioning
confidence: 99%